2013
DOI: 10.1371/journal.pone.0080873
|View full text |Cite
|
Sign up to set email alerts
|

Acteoside Suppresses RANKL-Mediated Osteoclastogenesis by Inhibiting c-Fos Induction and NF-κB Pathway and Attenuating ROS Production

Abstract: Numerous studies have reported that inflammatory cytokines are important mediators for osteoclastogenesis, thereby causing excessive bone resorption and osteoporosis. Acteoside, the main active compound of Rehmannia glutinosa, which is used widely in traditional Oriental medicine, has anti-inflammatory and antioxidant potentials. In this study, we found that acteoside markedly inhibited osteoclast differentiation and formation from bone marrow macrophages (BMMs) and RAW264.7 macrophages stimulated by the recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 51 publications
6
38
0
Order By: Relevance
“…Catalpol is considered to be a potential therapy for treatment of neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease (55). Acteosides suppress RANKL-mediated osteoclastogenesis by inhibiting c-Fos induction and the NF-κB pathway and by attenuating ROS production (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalpol is considered to be a potential therapy for treatment of neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease (55). Acteosides suppress RANKL-mediated osteoclastogenesis by inhibiting c-Fos induction and the NF-κB pathway and by attenuating ROS production (29).…”
Section: Discussionmentioning
confidence: 99%
“…the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway and attenuating the production of reactive oxygen species (ROS) (29). An extract of common Anemarrhena rhizome has antitumor, anti-inflammatory, and antioxidant action (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, it was found that isopsoralen Bone cells are a type of long-life cell, which is more susceptible to oxidative stress than osteoblasts and osteoclasts (20). Several experiments on rodents and humans have indicated that under oxidative stress induced by aging of the body, the number of bone cells gradually decreases, with weakened viability (21). The extracellular matrix in tissue is comprised of organic and inorganic components; the organic components are predominantly composed of a variety of collagens, whereas the inorganic components are hydroxyapatite crystals (5).…”
Section: Discussionmentioning
confidence: 49%
“…11 Previous phytochemical investigations on Rehmannia glutinosa Libosch led to the isolation of diverse biologically active compounds, and the majority of them are iridoids. [15][16][17][18] Most herbal medicines are administrated orally, so their components are inevitably in contact with microorganisms in the gut. 12 Catalpol exhibits a verity of pharmacological actions, such as anti-brain ischemia, anti-senile dementia, promoting neuro-remodeling, and reducing capillary permeability.…”
Section: Introductionmentioning
confidence: 99%